Volume 8: 32nd International Conference on Design Theory and Methodology (DTM) 2020
DOI: 10.1115/detc2020-22163
|View full text |Cite
|
Sign up to set email alerts
|

Novice Designers’ Approaches to Justifying User Requirements and Engineering Specifications

Abstract: User requirements and engineering specifications represent important criteria that engineering designers use to define their design problems and evaluate the suitability of their solution concepts. Novice designers frequently develop user requirements and engineering specifications as part of curricular design projects; however, few studies have explored how novice designers justify the user requirements and engineering specifications that they develop. This preliminary study analyzed the design reports of cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have shown that novice designers may also encounter broader difficulties related to gathering and applying information from stakeholders to inform their requirements development and/or solution development processes (Sugar 2001; Mohedas et al 2014, 2020; Conradie, De Marez & Saldien 2017; Loweth et al 2019, 2020 b ). For example, Mohedas et al (2014), in their study of capstone design students’ use of design ethnography, found that participants struggled to identify stakeholders who could provide needed design information.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that novice designers may also encounter broader difficulties related to gathering and applying information from stakeholders to inform their requirements development and/or solution development processes (Sugar 2001; Mohedas et al 2014, 2020; Conradie, De Marez & Saldien 2017; Loweth et al 2019, 2020 b ). For example, Mohedas et al (2014), in their study of capstone design students’ use of design ethnography, found that participants struggled to identify stakeholders who could provide needed design information.…”
Section: Introductionmentioning
confidence: 99%
“…Even when novice designers carry out framing activities, like research, they still may have an underdeveloped understanding of the problem and a lack of justification for their framing. In analyzing the reports of capstone design teams to understand the development and justification of user requirements and engineering specifications, Loweth et al [23] found that students' sources of information for user needs were often limited to interactions with sponsors and their own perceptions of user needs. Further, their engineering specifications were frequently derived from sponsor interaction, technical benchmarking, and prior work, and in some cases, specifications lacked a clear justification.…”
Section: Engineering Requirement Skills Of Novices and Expertsmentioning
confidence: 99%